The Politics of Sexuality and Women’s Inequality: Kate Millet’s Theoretical Analysis of the Short Story Lelaki ke-1000 di Ranjangku - Dhiya’Ulhaq, Mohammad Zharfa; Primadani, Kiki Malika (Proceedings of International Conference on Islamic Civilization and Humanities, 2026)
This study aims to deconstruct the meaning of feminism in the Islamic literary short story "Lelaki ke-1000 di Ranjangku" by Emha Ainun Najib, analyzed through Kate Millett’s Sexual Politics theory. The study employs a descriptive qualitative method, using the short story published in the anthology BH as its primary data source. The findings reveal that power in both public and domestic spheres is held by men, who position women as commodities within a capitalist economic system. The female narrator ("aku"), having been abandoned by her husband and lacking higher education, falls into prostitution as a means of survival, a condition further shaped by the vulnerability that came with her interfaith marriage. Despite her circumstances, she becomes widely sought after among male clients due to her physical appearance and warm disposition. Millett’s theory, which challenges the stereotypes and structures that oppress women, proves relevant in exposing how patriarchal power is reproduced through sexual and social relations in this narrative. The study concludes that the experiences of the female protagonist remain reflective of the realities faced by marginalized women in contemporary Indonesian society, and contributes to the growing body of feminist research in Indonesian Islamic literature.